Comparison of Economical and Social Development of Transition Countries - Budreikaitė, Danutė (Ekonomika, 1999)
The article gives the analysis of achievements of the most important Central and East European states, involved in the formation of a market economy, as relevant to the strategy of achieving the targeted goal. The analysis is aimed at revealing the advantages of transition to a market economy and possible costs. The period of 1985-1994 under analysis is the beginning of restructuring of the economy of the countries in transition and the point of turning. For comparative purposes, the basic economic, macroeconomic indicators, the growth of economy and structure, consumption, health care and education, State budget and payment balance, and other important economic and social indicators have been used that describe the level of economic and social development of state, its place in the world labour division. By using the comparative analysis attempts are made to relate the results of the economic and social development of the countries with the selected strategy of transition to a market economy. No doubt, various causes may have an effect on the economic and social achievements of the country, but this is logically inseparable from the strategy of the development of the country.